A history of autism conversations with the pioneers - Feinstein, Adam 1957- (Wiley online library, 2010)
"This book explores the history of autism from the first descriptions of autistic-type behaviour to the present day. Through unprecedented interviews with many of the earliest pioneers in the field, and leading professionals working today across the world - including China, India, Russia and Latin America - A History of Autism casts fresh light on the way in which this disorder is, and has been, perceived and treated. Meticulously researched, the book draws on evidence from previously unpublished documents and illustrations, as well as the latest findings and case studies. In addition, interviews with parents of autistic children confirm the essential contribution they have made to a more profound understanding of this enigmatic condition"--Provided by publisher.